2014
DOI: 10.1007/s40620-014-0086-8
|View full text |Cite
|
Sign up to set email alerts
|

Can tonsillectomy modify the innate and adaptive immunity pathways involved in IgA nephropathy?

Abstract: The benefits of tonsillectomy in IgA nephropathy (IgAN) are still debated. Tonsillectomy may remove pathogen sources and reduce the mucosal associated lymphoid tissue (MALT), limiting degalactosylated IgA1 (deGal-IgA1) production, which is considered to be the initiating pathogenetic event leading to IgA glomerular deposition. In the European network VALIGA, 62/1147 IgAN patients underwent tonsillectomy (TxIgAN). In a cross-sectional study 15 of these patients were tested and compared to 45 non-tonsillectomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…Tonsillectomy combined with steroid pulse therapy induced a 10% greater decrease in proteinuria than steroid pulse therapy alone, but this decrease was of marginal statistical significance, and whether it would lead to a subsequent beneficial effect on renal function is unclear. Consistent with the Japanese trial, a comparison of tonsillectomized patients with IgAN and non-operated matched controls with IgAN assessed in a study performed by the European VALIGA network failed to show any effects of tonsillectomy on circulating markers of innate immunity, ubiquitin-proteasome pathways and the pro-oxidative milieu 87 , or on clinical outcome 88 .…”
Section: Other Mucosal Diseasesmentioning
confidence: 66%
“…Tonsillectomy combined with steroid pulse therapy induced a 10% greater decrease in proteinuria than steroid pulse therapy alone, but this decrease was of marginal statistical significance, and whether it would lead to a subsequent beneficial effect on renal function is unclear. Consistent with the Japanese trial, a comparison of tonsillectomized patients with IgAN and non-operated matched controls with IgAN assessed in a study performed by the European VALIGA network failed to show any effects of tonsillectomy on circulating markers of innate immunity, ubiquitin-proteasome pathways and the pro-oxidative milieu 87 , or on clinical outcome 88 .…”
Section: Other Mucosal Diseasesmentioning
confidence: 66%
“…In contrast, outside of Japan, the efficacy of TMP in IgAN still remains controversial . Feehally et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, outside of Japan, the efficacy of TMP in IgAN still remains controversial. 36,37 Feehally et al 36 reported that there was no significant correlation between tonsillectomy and renal function decline in the European validation study of the Oxford classification of IgAN. The reason for this discrepancy is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…18 Observations have suggested that tonsillectomy could reduce the incidence of microhematuria and proteinuria in patients with normal renal function and mild proteinuria, 19,20 as well as the level of aberrantly galactosylated IgA1 in patients with IgAN. 21,22 However, the definitive pathogenic mechanism of tonsillitis in IgAN is still debated. We hypothesized that the overactive state of the tonsils and tonsillitis-mediated inhibition of immune tolerance might facilitate IgAN.…”
Section: Discussionmentioning
confidence: 99%